Perancangan Sistem Informasi Penjualan Peralatan Gaming Berbasis Web - Arjie Desmanto; Hari Sugiarto - UBSI (APMMI - Asosiasi Profesi Multimedia Indonesia, 2020)
Abstract - The Internet (Internconnected Network) is a term for a global computer network that connects one computer to another computer in the whole world. In various fields, especially in the business world today, the internet is one of the fastest media transactions. The number of internet users in the world has been very numerous, ranging from children, adolescents, and adults. Therefore, most people are more interested in choosing a practical lifestyle, including buying and selling transactions online through internet media. This allows the internet to become a means of conducting business activities and buying and selling transactions anytime and anywhere. Before the existence of the internet media, generally gaming equipment entrepreneurs carried out a system of selling, promotion, recording, and ordering merchandise still carried out manually. So even with consumers who have to visit the location of their favorite gaming equipment if you want while sifting through the categories of gaming equipment according to their respective interests. This makes consumers not benefited in terms of time and cost. So with the business of selling gaming equipment online, these things are likely to be avoided. The results of the research show that customers can more easily make purchases of gaming equipment online. Key Words: Selling Information System, Gaming Equipment Sales, Online Bussines Abstrak - Internet (Internconnected Network) adalah istilah untuk jaringan komputer global yang menghubungkan satu komputer ke komputer lain di seluruh dunia. Di berbagai bidang, terutama di dunia bisnis saat ini, internet adalah salah satu transaksi media tercepat. Jumlah pengguna internet di dunia sudah sangat banyak, mulai dari anak-anak, remaja, dan dewasa. Karena itu, kebanyakan orang lebih tertarik memilih gaya hidup praktis, termasuk transaksi jual beli online melalui media internet. Ini memungkinkan internet menjadi sarana untuk melakukan kegiatan bisnis dan transaksi jual beli kapan saja dan di mana saja. Sebelum adanya media internet, umumnya para pengusaha peralatan game melakukan sistem penjualan, promosi, pencatatan, dan pemesanan barang dagangan yang masih dilakukan secara manual. Begitupun dengan konsumen yang harus mengunjungi lokasi peralatan gaming favorit mereka jika Anda mau sambil menyaring kategori-kategori peralatan gaming sesuai dengan minat masing-masing. Ini membuat konsumen tidak diuntungkan dari segi waktu dan biaya. Jadi dengan bisnis penjualan peralatan game online, hal-hal ini kemungkinan besar akan dihindari. Hasil penelitian dimana pelanggan dapat lebih mudah melakukan pembelian pembelian peralatan gaming secara online. Kata Kunci: Perancangan Sistem Informasi, Penjualan Peralatan Gaming, Bisnis Online